2014
DOI: 10.1002/jmri.24533
|View full text |Cite
|
Sign up to set email alerts
|

Serial diffusion tensor imaging for early detection of radiation‐induced injuries to normal‐appearing white matter in high‐grade glioma patients

Abstract: DTI is not sensitive to acute global NAWM changes during the treatment of HGG, but sensitive to early posttreatment changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…DTI studies have been conducted in both adult and pediatric patients treated by either whole (7, 8) or partial brain RT (9-14), but only in selected WM structures, for example, corpus callosum (9) and corticospinal tracts (14). Overall, it is found that DTI changes are progressive over time and dose-dependent (9-12). Furthermore, a recent study showed a correlation between early diffusivity changes in the parahippocampal cingulum and a late decline in verbal recall (11).…”
Section: Introductionmentioning
confidence: 94%
“…DTI studies have been conducted in both adult and pediatric patients treated by either whole (7, 8) or partial brain RT (9-14), but only in selected WM structures, for example, corpus callosum (9) and corticospinal tracts (14). Overall, it is found that DTI changes are progressive over time and dose-dependent (9-12). Furthermore, a recent study showed a correlation between early diffusivity changes in the parahippocampal cingulum and a late decline in verbal recall (11).…”
Section: Introductionmentioning
confidence: 94%
“…Decreases in FA [18, 19, 30-32] and increases in AD, and RD [18, 33] have been observed in brain tumor patients treated with radiation. Unfortunately, the literature is sparse when it comes to the effects of surgery and chemotherapy on white matter integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for radiation-induced cognitive impairments remain obscure. In addition to disrupted neurogenesis and chronic inflammatory responses,47 radiotherapy is associated with a greater incidence of WM hyperintensities and may induce subtle progressive WM disturbance 48. Crucially, careful surgical preservation of tracts may theoretically be undone if radiotherapy compromises important proximal tracts.…”
Section: Relevance Of White Matter In Neuro-oncological Treatmentmentioning
confidence: 99%